2016
DOI: 10.5812/jssc.66785
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cutaneous Lichen Planus and Metabolic Syndrome: A Case-Control Study

Abstract: Background: Previous research declares that metabolic syndrome (MS) is a cluster of risk factors that contribute to a significant level of incidence of cardiovascular diseases and diabetes mellitus. Lichen Planus (LP) is a potential factor to affect dyslipidemia and other components of MS. Objectives: The aim of this research was to assess the association of MS, dyslipidemia, weight, hypertension, and diabetes mellitus with cutaneous LP. Methods: To reach the goal of this research, a case-control study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Egyptian Journal of Medical Research (EJMR), Volume 1, Issue2, 2020 As regard smoking, our results agree with Cassol-Spanemberg et al [9] who found that (73.4%) of patients were non-smokers; (26.6 %) of patients smoked, also Sadr Eshkevari et al [10] found that only (37.1%) of the participants were smokers.…”
Section: Discussionsupporting
confidence: 90%
“…Egyptian Journal of Medical Research (EJMR), Volume 1, Issue2, 2020 As regard smoking, our results agree with Cassol-Spanemberg et al [9] who found that (73.4%) of patients were non-smokers; (26.6 %) of patients smoked, also Sadr Eshkevari et al [10] found that only (37.1%) of the participants were smokers.…”
Section: Discussionsupporting
confidence: 90%
“…The pathogenesis of LS has been linked to increased oxidative damage and has been associated with autoimmune disorders and genetic factors, although how these contribute to systemic inflammation is not wholly understood 4,5 . We postulate that behavioural changes and chronic inflammation in LS may lead to systemic manifestations, including dyslipidaemia and an increased risk of hypertension (HTN), type II diabetes mellitus (DM2) and cardiovascular disease, as in other inflammatory conditions like psoriasis 1,2,6 . These and related conditions are grouped under metabolic syndrome (MS), which has a population prevalence of 20–30% and is more prevalent in women over the age of 50 years 7 .…”
Section: Ls Gls Egls Matched Cohort Ls Vs Matched Cohort Rr (95% Ci) ...mentioning
confidence: 99%
“…[89101112] Current published literature has emphasized that chronic inflammation, endocrine dysfunction, and oxidative stress, frequently associated with mucocutaneous disorders, may serve as potential predisposing risk factors for the development of the MS.[13] According to a recent study by Sadr Eshkevari et al , a majority of patients with LP presented with features of DM, hypertension, MS, and dyslipidemia [Table 2]. [14]…”
Section: Etiopathogenesismentioning
confidence: 99%